Float-stacked graphene–PMMA laminate - Kim, Seung Il; Moon, Ji Yun; Hyeong, Seok Ki; Ghods, Soheil; Kim, Jin Su; Choi, Jun Hui; Park, Dong Seop; Bae, Sukang; Cho, Sung Ho; Lee, Seoung Ki; Lee, Jae Hyun (Nature Communications, 2024)
Semi-infinite single-atom-thick graphene is an ideal reinforcing material that can simultaneously improve the mechanical, electrical, and thermal properties of matrix. Here, we present a float-stacking strategy to accurately align the monolayer graphene reinforcement in polymer matrix. We float graphene-poly(methylmethacrylate) (PMMA) membrane (GPM) at the water–air interface, and wind-up layer-by-layer by roller. During the stacking process, the inherent water meniscus continuously induces web tension of the GPM, suppressing wrinkle and folding generation. Moreover, rolling-up and hot-rolling mill process above the glass transition temperature of PMMA induces conformal contact between each layer. This allows for pre-tension of the composite, maximizing its reinforcing efficiency. The number and spacing of the embedded graphene fillers are precisely controlled. Notably, we accurately align 100 layers of monolayer graphene in a PMMA matrix with the same intervals to achieve a specific strength of about 118.5 MPa g−1 cm3, which is higher than that of lightweight Al alloy, and a thermal conductivity of about 4.00 W m−1 K−1, which is increased by about 2,000 %, compared to the PMMA film.